Simulations of decentration and tilt of a supplementary sulcus-fixated intraocular lens in a polypseudophakic combination using ray-tracing software - Łabuz, Grzegorz; Auffarth, Gerd U.; Yan, Weijia; Yildirim, Timur Mert; Khoramnia, Ramin (Photonics, 2021)
This study aimed to assess image quality after the tilt and decentration of supplementary intraocular lenses (IOLs) in a two-lens configuration. One was designed for sulcus fixation with a nominal power range of 1D-10D and was combined with a capsular fixation 20D IOL. The optical performance of a ray-tracing model was tested under IOL misalignment through the area under the modulation transfer function (MTFa) and wave aberrations. Tilting by 10 degrees resulted in a 4% reduction of the MTFa for a 10D IOL as compared to 9% for the 20D lens. The two models demonstrated good tolerance to a 1 mm decentration; as for the 10D sulcus-fixated lens, the MTFa loss was 2%, and 4% for the capsular fixation lens. Coma and astigmatism increased three- and four-fold, respectively, after a 10 degrees tilt compared to the aberration level induced by the 1 mm decentration. Both analyses showed a trend towards a lower MTF impact and fewer optical errors with decreasing nominal power. In conclusion, when misaligned, low-power sulcus-fixated IOLs might retain their good optical quality. An extreme tilt of 10 degrees has a more detrimental effect on the IOL performance than a 1 mm decentration. The proper alignment of a high-power capsular fixation lens is important in achieving a desirable postoperative outcome.